2023
DOI: 10.15280/jlm.2023.13.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Nutrition, Physical Activity, and Sleep Hygiene to Promote Cardiometabolic Health of Airline Pilots: A Narrative Review

Abstract: Background Airline pilots experience unique occupational demands that may contribute to adverse physical and psychological health outcomes. Epidemiological reports have shown a substantial prevalence of cardiometabolic health risk factors including excessive body weight, elevated blood pressure, poor lifestyle behaviors, and psychological fatigue. Achieving health guidelines for lifestyle behavior nutrition, physical activity, and sleep are protective factors against the development of noncommunic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 142 publications
0
7
0
Order By: Relevance
“…Furthermore, H. pylori infection has been linked to various extraintestinal manifestations, such as CVD, obstructive sleep apnea syndrome, and metabolic syndrome [29]. These are conditions that have been previously reported in the pilot population [6][7][8], adding to the significance of this association. Another intriguing observation is the connection between H. pylori and motion sickness.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, H. pylori infection has been linked to various extraintestinal manifestations, such as CVD, obstructive sleep apnea syndrome, and metabolic syndrome [29]. These are conditions that have been previously reported in the pilot population [6][7][8], adding to the significance of this association. Another intriguing observation is the connection between H. pylori and motion sickness.…”
Section: Discussionmentioning
confidence: 83%
“…Intriguingly, studies have demonstrated a potential association between the seroprevalence of anti-HSV-1 antibodies and CVD [ 17 - 19 ]. Remarkably, the burden of cardiovascular risk factors appears to be significantly elevated among APs [ 7 , 8 , 20 ]. In a cohort study conducted by Siscovick et al [ 17 ] in the United States, it was discovered that older individuals with IgG antibodies against HSV-1 were twice as likely to experience myocardial infarction and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially significant as it allows for the early detection of NAFLD in seemingly healthy pilots, enabling timely intervention through evidence-based interventions targeting nutrition, physical activity, and sleep hygiene. [ 28 ] Considering the critical role APs play in ensuring the safety of millions of travelers globally, [ 4 ] it is imperative to prioritize providing guidance and support to overweight pilots. Furthermore, prospective studies are needed to further evaluate the usefulness of LSM and CAP as imaging biomarkers for predicting clinical cardiometabolic outcomes in this occupational group.…”
Section: Discussionmentioning
confidence: 99%
“…Airline pilots face distinctive occupational circumstances that are marked by irregular schedules, prolonged periods of wakefulness, and extended exposure to ultraviolet and cosmic radiation [11,12] Such conditions are recognized contributors to an increased risk of cardiometabolic disorders and malignant melanoma [11,12], all conditions that could be closely linked to compromised autophagy flux [13][14][15]. Additionally, construction workers who are regularly exposed to environmental contaminants like particulate matter and toxic metals may also experience an increase in autophagic flux as a protective response [16].…”
Section: Introductionmentioning
confidence: 99%